(3MGTjI Ydi TQM (B( (3HGfJ SYGO (B) (3dGHf gTGe GdCfUGQis - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s; (3LeGd GdOjf CHh eMeO YHO Gddg jhSa Hf gTGes ((3eMeO GdbWQi s)
(3ChdgG (B:s
(3GdMeO ddg CeG HYO , ajbhd YHO GdbGOQ GdHZOGOi (B: (3gPg ahGFO LeYJgG Mjf bQC Ydi HYV GdENhGf TQM bUjOI HGfJ SYGO dcYH Hf RgjQ GdUMGHi s
(3BNQgG (B:s
(3hbO eVi Gdbhd ai Pdc Cbhd eVi YfO TQM bhdg (B:( (3cGfJ ehGYjO YQbhH dgG hPcQg CjVkG ah ehGVY HYOg hgPG BNQ eG CQOfG GjVGMg LYdg Gddg NGdUkG dhLgg GdcQje s
(3aQZ ef JCdjag SfI (B1082s
(3bUjOI HGfJ SYGO dcYH Hf RgjQ Hf CHj SdeI GdeRfis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdCOHs